2021
DOI: 10.2147/ijgm.s329733
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Profiling of KDM5 Subfamily Signature in Non-Small-Cell Lung Cancer

Abstract: Background: Despite improvements in diagnosis and treatment, lung cancer is one of the most lethal human diseases, with a dismal 5-year relative survival rate of only 5% for patients diagnosed with advanced metastatic disease. Accumulating evidence supports that epigenetic aberration of histone demethylase-KDM5 subfamily is linked to human pancancer. However, the detailed functions of KDM5 proteins in lung cancer, especially in nonsmall-cell lung cancer (NSCLC), remain poorly understand. Methods: UALCAN, GEPIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Prognostic analysis revealed that KDM5 family members were strongly associated with relevant clinicopathological factors and prognosis. A previous study has confirmed that alterations in the KDM5 gene family may affect the prognosis of patients with non-small cell lung cancer 26 . There is increasing evidence suggesting that deregulation of KDM5 family may have important phenotypic consequences in various types of cancer, including the role of KDM5 family demethylases in the emergence of drug tolerance 27 .…”
Section: Discussionmentioning
confidence: 74%
“…Prognostic analysis revealed that KDM5 family members were strongly associated with relevant clinicopathological factors and prognosis. A previous study has confirmed that alterations in the KDM5 gene family may affect the prognosis of patients with non-small cell lung cancer 26 . There is increasing evidence suggesting that deregulation of KDM5 family may have important phenotypic consequences in various types of cancer, including the role of KDM5 family demethylases in the emergence of drug tolerance 27 .…”
Section: Discussionmentioning
confidence: 74%
“…KDM5B has an ambivalent role in oncogenesis, behaving as an oncogene in some cancer cell lines and as a tumor suppressor in others [ 12 , 36 ]. This could partly depend on the pattern of the isoforms expressed in different cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It is an attractive target in cancer therapy. Several prospective raw letter analyses have shown that KDM5 is closely associated with regulaing immune infiltration and expressing immune-related molecules, and is considered a prospective candidate for epigenetic anti-tumor therapy ( 117 119 ). In clinical treatment, some patients have low tumor cell PD-L1 abundance, so they cannot respond well to ICB.…”
Section: Classification and Biological Functions Of Histone Methyltra...mentioning
confidence: 99%